The role of school management in ICT implementation on student achievement and teacher attitudes in the Arab sector in Israel - Horany, Hana (Technium Social Sciences Journal, 2024)
This study aims at evaluating the effectiveness of school management in the integration of ICTs within the schools with emphasis on students’ performance and teachers’ perception. The data were obtained from questionnaires and interviews conducted on 11 high schools in the Arab and Bedouin localities of Israel. This study shows that strategic management, structural design, and leadership enhance students’ performance especially in Mathematics and English. The schools that have well defined policies on ICT and good leadership achieved high levels of student engagement and better academic performance. However, the study reveals that some inequality prevails in the system; the northern schools are in a better condition as compared to the Bedouin schools in the south where inadequate resources and cultural barriers are also seen. Leadership was found to be the most important variable affecting the teachers’ perception on ICT use in teaching and learning process; particularly the hybrid leadership practices positively affected the teachers’ involvement and student achievement. The findings imply that more leadership and specific strategies are required to support effective integration of ICTs in the underprivileged areas